O auxílio emergencial na pandemia da covid-19 no Brasil: uma política de renda transicional a caminho da renda básica universal. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The Brazilian socioeconomic scenario is marked by inequality, structural unemployment and the insufficiency of welfarist policies, evidencing the exhaustion of the wage relationship as the only possibility to obtain income, - especially in the context of the real subsumption of work, which imposes the productivity and participation of all. in the construction of a wealth that is not socially distributed. This context is strained by the Covid-19 pandemic, which in addition to intensifying academic and political debates on Universal Basic Income in Brazil and in the world due to the need for isolation and social distancing as preventive measures to the proliferation of the virus, resulted in the approval of Emergency Aid, applied from April 2020, with payment of R$ 600,00 (six hundred reais) to approximately seventy million Brazilians. Among its impacts are the reduction of poverty, extreme poverty and inequality, as well as a multiplier effect in benefit of consumption, tax collection and, consequently, the mitigation of the crisis experienced in the pandemic, with positive effects on Brazilian GDP. In addition to these socioeconomic repercussions, political developments were noticeable, with the proposal of new bills for the creation of income transfer policies, regulation of Basic Income or conversion of Emergency Aid into permanent, and legal, by the judgment of the Writ of Injunction by the Federal Supreme Court, ordering the Executive Branch to regulate and apply the Citizen's Basic Income. From such impacts, this thesis will aim to demonstrate the elements that characterize Emergency Aid as a transition policy to Universal Basic Income. Therefore, this interdisciplinary research, of a socio-legal nature, with a qualitative approach and application of document analysis, will adopt as methodological procedures the bibliographic research, to examine the theoretical bases that justify the Universal Basic Income, in particular the post-operaist theoretical framework, marked here for the perspectives on cognitive capitalism, the real subsumption of work and the refusal to work, as well as documental research, with analysis of reports and research from IBGE, IPEA and DIEESE, among other entities, on the issue of income and work in Brazil, before and during the pandemic - including, considering the repercussions arising from the Emergency Aid. The time frame of the research will be concentrated between April and August 2020, months in which the highest amount was paid as Aid and to more beneficiaries, that is, with less conditionalities. The investigation has as its territorial cut the Brazilian territory, in which the aforementioned Emergency Aid was paid. It is expected as a result the exposition of elements that characterize the Aid as a transition policy towards the adoption of the Universal Basic Income.
Keywords: Renda Básica Universal; Auxílio Emergencial; Políticas de renda; Renda; Pandemia da Covid-19; Universal Basic Income; Emergency Aid; Income policies; Income; Covid19 Pandemic; CNPQ::CIENCIAS SOCIAIS APLICADAS